ВПЛИВ МУЗЕЙНОЇ ПЕДАГОГІКИ НА ФОРМУВАННЯ НАЦІОНАЛЬНИХ ЦІННОСТЕЙ ОСОБИСТОСТІ - Філіпчук Наталія Олександрівна (International Journal of Innovative Technologies in Social Science, 2020)
The article analyzes the museums' role in shaping the citizens’ state consciousness, person’s national values and in culture- educational activities. The basic principles of formation the museum pedagogy’s ideological and functional orientation are revealed. It is determined that the museum pedagogy’s leading function is the influence on the visitor’s logical and emotional sphere, his outlook, convictions. The idea that museum pedagogy forms the integrative fields for the improvement of formal and informal educational spaces and helps to fill qualitatively the logical-cognitive and sensory process of personal development with new knowledge and meanings is substantiated. The article stressed that school or any other educational institution that restricts its activities by a narrow local area and is not integrated into socio-cultural environment institutes, is ineffective, unable to ensure the completely quality of educational work. The European countries experience of mainstreaming the museum pedagogy in the cultural and educational space is described.